Reflection coefficient for two elastic layers joining two homogeneous materials - WESOŁOWSKI, Z. (Archives of Acoustics, 1993)
Two homogeneous elastic layers are situated between two homogeneous elastic materials. The reflection coefficient for the harmonic wave depends on the elastic constants of the layers and the frequency. The formula is too complex for an analytical treatment. Two situations were analysed numerically. In the first one, thicknesses of the layers were kept constant, and the speeds leading to constant reflection coefficient were calculated. In this case the reflection coefficient either has no minimum, or its minimum equals zero. In the second situation, propagation speeds were constant, and the thickness leading to constant reflection coefficient were calculated. There exist minima equal to zero, and maxima equal to the reflection coefficient for the long-wave limit.